THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, COMPANY CHARACTERISTICS, AND PROFITABILITY ON COMPANY VALUES (Case Study on Non-Financial State-Owned Enterprises listed on the Indonesia Stock Exchange for the 2018-2021 period) - Saputri, Indah Yuliana; Ariani, Kurnia Rina (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Company value is the investor's perception of the company formed through stock market indicators. High company value indicates that the company has good performance and future prospects that can be trusted by investors. This study aims to determine the factors that influence company value, including good corporate governance, company characteristics and profitability. This research is a quantitative study. The population used in this study is data on non-financial state-owned companies listed on the IDX during the 2018-2021 period. Sampling in this study used the purposive sampling method, obtaining 62 research samples. Multiple linear regression analysis (multipler linear regression method) was used in this study as an effort to answer the problems in the study. The results showed that managerial ownership, independent commissioners, audit committees, institutional ownership, company size and profitability simultaneously had a significant effect on the company value variable in non-financial state-owned companies listed on the IDX during the 2018-2021 period. While partially, only the audit committee and institutional ownership influenced the company value. The variables of managerial ownership, independent commissioners, company value, and profitability did not affect the company value. Keywords: Good corporate governance, Company characteristics, Company value, Profitability